2014
DOI: 10.3390/atmos5020435
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PM10 and PM2.5 and Their Metals Content in Different Typologies of Sites in South-Eastern Italy

Abstract: Samples of PM 10 and PM 2.5 were collected discontinuously between 2003 and 2010 at fifteen monitoring sites (urban, background, industrial) in the south-eastern part of Italy using a mobile laboratory. In total, 483 PM 10 and 154 PM 2.5 samples were collected and chemically analyzed for the determination of metal content. Data were used to investigate concentration differences among the typologies of sites, the seasonal patterns, and the influence of advection of Saharan dust (SD). PM 10 and PM 2.5 average c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
29
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 39 publications
(66 reference statements)
7
29
0
2
Order By: Relevance
“…As is often linked in literature to the use of fossil fuel (traffic, domestic heating, natural gas, etc.). Ni is often described as a trace element in petroleum but it is also derived from the burning of lubricant oil [42], then the above mentioned differences between the concentrations registered during the autumn/winter and spring/summer semesters should be correlated to heating. Cr shows many anthropogenic sources, in particular coal burning and waste incineration [43].…”
Section: Enrichment Factormentioning
confidence: 99%
“…As is often linked in literature to the use of fossil fuel (traffic, domestic heating, natural gas, etc.). Ni is often described as a trace element in petroleum but it is also derived from the burning of lubricant oil [42], then the above mentioned differences between the concentrations registered during the autumn/winter and spring/summer semesters should be correlated to heating. Cr shows many anthropogenic sources, in particular coal burning and waste incineration [43].…”
Section: Enrichment Factormentioning
confidence: 99%
“…Air pollution is a general problem that must be taken seriously Lary et al, 2014). Many studies have attempted to characterise the particulate air pollution from industrial and traffic sources (Contini et al, 2014;López et al, 2011) by using source apportionment approaches that identify different sources in the receptor points of sampling (Herrera Murillo et al, 2013;Gugamsetty et al, 2012;Khodeir et al, 2012). Marchetti et al (2014) evaluated children breathing symptoms in relation to industrial atmospheric pollution based on geographical proxy measures for exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have confirmed the close relationships between the high concentrations of TSP, PM 2.5 and an increased risk of respiratory symptoms, cancer and even mortality rates [1][2][3][4]. Besides their adverse effects on visibility [5], TSP and PM 2.5 have been found to be the carriers of pathogenic bacteria that lead to fatal diseases [6] and toxic metals that result in human dysfunction and various diseases [4,7,8].…”
Section: Introductionmentioning
confidence: 91%